De concordia inter Codices - Consent between codes - SIENNICKI, MICHAŁ (Prawo Kanoniczne, 2019)
Apostolic Letter issued 'Motu Proprio' “De concordia inter Codices” modifying some norms of the Code of Canon Law The following article attempts to explain the reasons why the Supreme Legislator of the Church has decided to promulgate the apostolic letter in the form of a motu proprio, De concorida inter Codices. It presents a brief history of the preparation of the text and the problems concerning its promulgation, both for the universal Church and in the particular case of Poland. The author of the article tries to show the need for knowledge of the new canonical norm already desired by Pope Benedict and finally promulgated by Pope Francis. Canonical science cannot be limited only to the Latin code but must go beyond this to the Eastern code, especially when it comes to matters of marriage and its validity, the sacrament of baptism and enrolment in a Church sui iuris. These are indispensable elements of canonical science that every pastor of the Church must possess and especially those who meet the Eastern faithful in their pastoral circumstances. It is to be hoped that canonical science will help to give pastoral care to all the faithful who await it.